Identification, Genetic Analysis and Mapping of Resistance to Phytophthora sojae of Pm28 in Soybean - WU, Xiao-ling; ZHANG, Bao-qiang; SUN, Shi; ZHAO, Jin-ming; YANG, Feng; GUO, Na; GAI, Jun-yi; XING, Han (Agricultural sciences in China, 2011)
Phytophthora sojae Kanfman and Gerdemann （P. sojae） is one of the most prevalent pathogens and causes Phytophthora root rot, which limits soybean production worldwide. Development of resistant cultivars is a cost-effective approach to controlling this disease. In this study, 127 soybean germplasm were evaluated for their responses to Phytophthora sojae strain Pm28 using the hypocotyl inoculation technique, and 49 were found resistant to the strain. The hypocotyl of P1, P2, F1, and F2：3 of two crosses of Ludou 4 （resistant）×Youchu 4 （susceptible） and Cangdou 5 （resistant）×Williams （susceptible） were inoculated with Pm28, and were used to analyze the inheritance of resistance. The population derived from the cross of Ludou 4×Youchu 4 was used to map the resistance gene （designated as Rps9） to a linkage group. 932 pairs of SSR primers were used to detect polymorphism, and seven SSR markers were mapped near the resistance gene. The results showed that the resistance to Pm28 in Ludou 4 and Cangdou 5 was controlled by a single dominant gene Rps9, which was located on the molecular linkage group N between the SSR markers Satt631 （7.5 cM） and Sat_186 （4.3 cM）.